2000
DOI: 10.1017/s0021963099005235
|View full text |Cite
|
Sign up to set email alerts
|

The Mental Health of the Peers of Suicide Completers and Attempters

Abstract: This study examined the prevalence and risk of psychiatric disturbances and suicidal behaviours among the peers of suicide attempters and completers. The subjects were selected from high schools with and without history of student suicides in the past 3 years. The psychiatric disturbances (as measured by the YSR and CBCL), suicidal behaviours, drug use, and a wide range of potential risk factors were measured. About a quarter of the peers of suicide completers and attempters were probable psychiatric cases and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 0 publications
2
38
0
Order By: Relevance
“…Our findings are consistent with studies observing an association between exposure status and increased likelihood of suicidal behavior 6,[10][11][12][13][14][15][16][17][18][19][21][22][23][24] , but do not support a casual pathway for exposure via imitation where the exposure must necessarily precede the imitative attempt. Despite finding that any lifetime exposure increased the likelihood of being a suicide attempter, when we examined only exposures that occurred before the age of first suicide attempt in attempters and before the same age in matched controls we found that exposure was not associated suicide attempter status.…”
Section: Discussion Exposure and Risk For Suicide Attemptsupporting
confidence: 89%
See 4 more Smart Citations
“…Our findings are consistent with studies observing an association between exposure status and increased likelihood of suicidal behavior 6,[10][11][12][13][14][15][16][17][18][19][21][22][23][24] , but do not support a casual pathway for exposure via imitation where the exposure must necessarily precede the imitative attempt. Despite finding that any lifetime exposure increased the likelihood of being a suicide attempter, when we examined only exposures that occurred before the age of first suicide attempt in attempters and before the same age in matched controls we found that exposure was not associated suicide attempter status.…”
Section: Discussion Exposure and Risk For Suicide Attemptsupporting
confidence: 89%
“…We found no other studies that adequately addressed the temporal sequence of exposure and suicidal behavior in the exposed. Most did not describe temporal sequence at all 6,10,11,13,[16][17][18][19]22,24,25,29 , or only that there were limited exposures and/or attempts within 12 months prior to assessment, excluding possible earlier exposures and attempts 4,5,12,14 . In a prospective study, Lewinsohn et al assessed baseline exposure and suicidal behavior at a subsequent timepoint, but did not address the relationship of baseline exposure to prior suicide attempt, thus preventing any clear establishment of temporality necessary to infer causality 23 .…”
Section: Discussion Exposure and Risk For Suicide Attemptmentioning
confidence: 99%
See 3 more Smart Citations